Global Absolute Poverty: The Evolution of its Measurement - Michail Moatsos (ZBW – Leibniz Information Centre for Economics, 2020)
In estimating the incident of global poverty, both contemporarily and historically, one needs to reach far into the domain of assumptions and second best approaches. This paper navigates through this methodological jungle. This discussion of the literature, although extensive is not exhaustive, as several of the problems discussed below can fill lengthy chapters on their own. The focus is solely on the absolute poverty concept from the perspective of the dollar-a-day approach, which is the dominant in the global poverty literature.
Keywords: I32; 330; Global Poverty; Dollar-a-day; Poverty Lines; Absolute Poverty